Pulmonary artery catheterization. (June 2022) - Naneishvili, Tamara; Cosbey, Lucy; Butler, Rob
Abstract: The use of pulmonary artery catheters has reduced in recent years, but is increasing in cardiac catheterization laboratories. They are used in the management of critically ill patients in critical care units, and for the investigation of breathlessness and pre-transplant assessment. We summarize the roles and issues related to pulmonary artery catheterization.